Language teachers’ narratives and professional self-making - Reichmann,Carla Lynn (2019)
ABSTRACT This article addresses language teacher education, considering the relevance of implicit and explicit theories, methodological choices, teacher representations and practices. Specifically, the purpose is to report and discuss studies developed by two researchers who work with narratives and focus on language teacher development, teacher literacy (Kleiman & Matencio, 2005) and identity construction (Barkhuizen, 2017). Thus, a panoramic view of work in progress is offered, and the field for novice and experienced educators in Brazil is problematized. As a result, the authors understand that teacher awareness-raising and transformations have been successfully enabled, which is confirmed by the several deriving publications mentioned.